2022
DOI: 10.1002/ccd.30213
|View full text |Cite
|
Sign up to set email alerts
|

Novel oral anticoagulants versus vitamin K antagonists in patients with atrial fibrillation after transcatheter aortic valve replacement: A systematic review and meta‐analysis

Abstract: Background The efficacy and safety of novel oral anticoagulants (NOACs) compared to the current guideline‐recommended vitamin K antagonists (VKAs) in atrial fibrillation (AF) patients undergoing transcatheter aortic valve replacement (TAVR) has not been well established. We pooled evidence from all available studies to assess the risks and benefits of this drug class. Methods We queried electronic databases (MEDLINE, Scopus, and Cochrane central) up until January 28th, 2022 for studies comparing NOACs to VKAs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…33 Another meta-analysis conducted by Memon et al showed no significant difference in stroke or systemic embolism, all-cause mortality, major bleeding, intracranial hemorrhage, and myocardial infarction between NOACs versus VKAs for AF patients undergoing TAVI. 32 Our metaanalysis revealed that the patients prescribed NOACs had a lower incidence of bleeding and intracranial bleeding. However, sensitivity analyses found that the effects of NOACs and VKAs were equivalent in bleeding and intracranial bleeding after the exclusion of Tanawuttiwat et al study.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…33 Another meta-analysis conducted by Memon et al showed no significant difference in stroke or systemic embolism, all-cause mortality, major bleeding, intracranial hemorrhage, and myocardial infarction between NOACs versus VKAs for AF patients undergoing TAVI. 32 Our metaanalysis revealed that the patients prescribed NOACs had a lower incidence of bleeding and intracranial bleeding. However, sensitivity analyses found that the effects of NOACs and VKAs were equivalent in bleeding and intracranial bleeding after the exclusion of Tanawuttiwat et al study.…”
Section: Discussionmentioning
confidence: 81%
“…The largest observational study by Tanawuttiwat et al was not included in prior meta-analysis. 32 Interestingly, the patients prescribed NOACs tended to have a lower incidence of all-cause mortality with the RRs less than 1 despite no statistical difference. Qualitative analysis showed that the three studies might be the source of the large heterogeneity of all-cause mortality, yet meta-regression did not find the specific factors leading to heterogeneity.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…83 A subsequent meta-analysis comparing NOACs to warfarin after TAVR in patients with atrial fibrillation found no significant difference in stroke or systemic embolism, major bleeding, or all-cause mortality. 84…”
Section: Preventive Strategies For Special Patient Populationsmentioning
confidence: 99%